Review on Alzheimer’s disease: past, present and future - Rayathala, Jessy; C, Kiran Kumar; P, Venkatesh (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2022)
Alzheimer’s disease is a progressive neurodegenerative disorders that is the six leading Cause of death and the most common cause of dementia worldwide. The most common cause of dementia is Alzheimer’s disease (AD). Accounting for nearly 60 to 80 % of all cases. AD is the six leading cause of death with an estimated prevalence of nearly 30 million people worldwide. Age is the most important risk factor for AD, with an exponential increase in prevalence from 3 to 32 % from the ages 65 to 85 years old. An estimated 5.6 million individuals over the age of 65 suffer from AD in the United States, a number projected to nearly triple to 13.8 million by 2050 due to increase in population. The 2000s ushered in a focus on the study of prodromal stages of neurodegerative disease before the full – blown dementia syndrome. The current decades have been the rise of imaging and other biomarkers to characterize preclinical disease before the development of significant cognitive decline. Finally, we suggest future directions and predictions for dementia related research and potential therapeutic interventions.